Inventario de Ansiedad ante Exámenes (versión en español): diferencias según sexo y valores normativos en universitarios de Lima - Domiguez-Lara, Sergio (2019)
The aim of this paper was analyze the measurement invariance of Test Anxiety Inventory (Spanish Version: TAI-S) between men and women, and the obtention of normative data in college students from Lima. Were evaluated 866 college students (71.1 % women) with aged between 17 and 52 years (M = 20.38). The measurement invariance was performed with multigroup confirmatory factor analysis, which shows that degree of measurement invariance is enought for claim that the measurement is the same among men and women. Same way, the reliability coefficients (α, ω y H) have high magnitude. The normative data were elaborated with percentiles because the TAI-S scores don’t have normal distribution. The results are discussed and practical guidelines are given for the use of the norms.